Development of Calculus Teaching Material: Context of Universitas Timor, Indonesia - Yohanis Ndapa Deda; Hermina Disnawati (Universitas Ahmad Dahlan, 2020)
This research development aims to producing a valid, practical, and useful deferential calculus teaching material. The teaching material referred to this study is a student worksheet with a constructivism approach. Itapplied development research method with formative research type. It was conducted in two stages, namely preliminary analysis and formative evaluation stage.The results of the experts'validation stated that the teaching material developed has reached thecorrect category. The results of one-on-one trials class indicate that the developed the material can be accepted and be used. Furthermore, field trial results, which was conducted to see the effectiveness aspect, have met the criteria. In the other world, the current research has produceda valid, practical, and usefulderivative calculus teaching material that focuses on teaching material and its supporting components, including syllabus, and lesson plans.